2016
DOI: 10.1177/1352458516681862
|View full text |Cite
|
Sign up to set email alerts
|

Operationalising cognitive fatigability in multiple sclerosis: A Gordian knot that can be cut?

Abstract: Background: Researchers have attempted to operationalise objective measures of cognitive fatigability in MS to overcome the perceived subjectivity of patient reported outcomes of fatigue (PROs). Measures of cognitive fatigability examine decrements in performance during sustained neurocognitive tasks.Objective: This editorial briefly summarises available evidence for measures of cognitive fatigability in MS and considers their overall utility.Results: Findings Studies suggest there may be a construct that is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Both forms of fatigue can be separated into an effort-independent general subjective sensation of fatigue, and fatigability as an effort-dependent change in performance. 5 Functional imaging work on different fatigue types 6 provided at least in part conflicting results. Some found a correlation between fatigue and brain atrophy or lesion load.…”
Section: Introductionmentioning
confidence: 99%
“…Both forms of fatigue can be separated into an effort-independent general subjective sensation of fatigue, and fatigability as an effort-dependent change in performance. 5 Functional imaging work on different fatigue types 6 provided at least in part conflicting results. Some found a correlation between fatigue and brain atrophy or lesion load.…”
Section: Introductionmentioning
confidence: 99%
“…Third, they suggested that research explore whether the more promising CF measures are correlated with impaired functioning after accounting for possible confounds. Fourth, they highlighted the need for outcome assessments to be able to identify clinically meaningful improvement [109]. A last point made by Harrison et al that we wish to echo here is that the quest for improving the objective measurement of CF does not imply that subjectively measured fatigue is somehow less relevant or important [109].…”
Section: Discussionmentioning
confidence: 97%
“…As previously stated, the study of fatigue in neurological conditions is fraught with varying definitions and methodology that highlight the need for a clear conceptual framework from which to guide further study. Harrison et al [109] summarized the available evidence for measures of CF in MS and made the following recommendations. First, they called for the development of a guiding theory of CF that considers differences between primary and secondary fatigue and broader psychosocial models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is still debated whether cognitive fatigability may represent an aspect of cognitive impairment rather than a distinct phenomenon. Within this framework, the lack of reliable measures and the need for an objective index of cognitive fatigability have been highlighted (Harrison, das Nair, & Moss‐Morris, ). An accurate characterization of all aspects of fatigue, indeed, may guide in the selection of specific and tailored treatments (Manjaly et al , ).…”
mentioning
confidence: 99%